Higher modes and superposed mode behavior for flexible pavement layer system - Ismail, Norfarah Nadia; Md Yusoff, Nur Izzi; Wan Azahar, Wan Nur Aifa; Ramli, Ahmad Bukhari; Md Husain, Nadiah; Kasim, Norhidayu (IOP Publishing, 2020)
This paper presents the study of modes behavior in pavement layer system using Common Array Profiling Spectral Analysis of Surface Waves (CAP-SASW) testing method. Method for evaluation and testing the materials at pavement sites are traditionally destructive. The utilization of non-destructive method such as CAP-SASW is a very useful advantage, however deeper study on its mode behavior for pavement layer is not proven. Comparing both theoretical and experimental generated modes, this paper aims to provide precise configuration measurement in sampling pavement materials besides understanding its modes behavior.